HER2 expression in urothelial carcinoma, a systematic literature review - Scherrer, Emilie; Kang, Ashley; Bloudek, Lisa M.; Koshkin, Vadim S. (Frontiers in Oncology, 2022)
Background: Urothelial carcinoma (UC) is a common malignancy with significant associated mortality. Recent clinical trials suggest an emerging role for HER2-targeted therapy. Testing for HER2 expression in UC is not part of current routine clinical practice. In consequence, the prevalence of HER2 expression in UC is not well defined. Methods: A systematic literature review (SLR) was conducted to characterize HER2 expression in both locally advanced unresectable or metastatic (LA/mUC) and earlier stage UC, classified as HER2+, HER2-low, HER2-. HER2+ was defined as an immunohistochemistry (IHC) score of 3+ or IHC 2+ and ISH/FISH+. HER2-low was defined as an IHC score of 2+ and ISH/FISH- or IHC 1+. HER2- was defined as an IHC score of 0. Weighted averages were calculated to generate an estimate of the population prevalence. Results: A total of 88 studies were identified, with 45 and 43 studies investigating LA/mUC and earlier stage UC, respectively. The most common assays used were Dako HercepTest and Ventana Pathway anti-HER2/neu (4B5) for IHC to assess HER2 protein expression; Abbott PathVysion HER-2 DNA Probe Kit, FoundationOne CDx, and Guardant360 CDx for assessing HER2 gene amplification. The most frequently cited scoring guidelines were ASCO/CAP guidelines for breast cancer and gastric cancer, though most studies defined their own criteria for HER2 expression. Using the pre-specified definition, HER2+ prevalence ranged from 6.7% to 37.5% with a weighted average of 13.0% in LA/mUC. Only 1 study presented data that could be classified as HER2+ based on pre-specified criteria in earlier stage UC patients, and this study represented a likely outlier, at 76.0%. Conclusion: The results from this SLR help to shed light on HER2 expression in UC, a potentially clinically relevant biomarker-driven subpopulation for emerging HER2-directed regimens. Results of this SLR illuminate the variability in how HER2+ status expression levels are being assessed and how HER2+ is defined. Consensus on standardized HER2 testing and scoring criteria is paramount to better understand the clinical relevance in patients with UC.